Neuropathic Symptoms in World Trade Center Disaster Survivors and Responders. Issue 1 (January 2016) - Wilkenfeld, Marc; Fazzari, Melissa; Segelnick, Jacqueline; Stecker, Mark
Abstract : Objective: The objective of this research is to determine whether responders and survivors of the World Trade Center (WTC) disaster experience symptoms of neuropathy at a rate higher than those not exposed. Methods: A survey of neuropathic symptoms in patients who were and were not exposed at the WTC based upon the Michigan Neuropathy Screening Instrument (MNSI). Results: Even after correction for medical comorbidities, age, and depression, neuropathic symptoms are much more common in those exposed to WTC dust and increase with increasing exposure. Conclusions: This study provides evidence that exposure to WTC dust is associated with neuropathic symptoms.